2021
DOI: 10.1096/fj.202002652rr
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1 induction during kidney injury promotes fibrotic epithelial dysfunction via deregulation of klotho, p53, and TGF‐β1‐receptor signaling

Abstract: Renal fibrosis leads to chronic kidney disease, which affects over 15% of the U.S. population. PAI‐1 is highly upregulated in the tubulointerstitial compartment in several common nephropathies and PAI‐1 global ablation affords protection from fibrogenesis in mice. The precise contribution of renal tubular PAI‐1 induction to disease progression, however, is unknown and surprisingly, appears to be independent of uPA inhibition. Human renal epithelial (HK‐2) cells engineered to stably overexpress PAI‐1 underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…This is in line with the results observed in this study, which showed that the number of cells in G2/M phase increased in HK-2 cells treated with myoglobin and decreased treated with tocilizumab. Similarly, some study has shown that the cell cycle arrest and brosis induced by renal tubular epithelium are related to the PAI-1-Klotho-p53-dependent mechanism, overexpression of PAI-1 increased the total p53 protein level [30]. The above theories further demonstrate our experimental viewpoint.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is in line with the results observed in this study, which showed that the number of cells in G2/M phase increased in HK-2 cells treated with myoglobin and decreased treated with tocilizumab. Similarly, some study has shown that the cell cycle arrest and brosis induced by renal tubular epithelium are related to the PAI-1-Klotho-p53-dependent mechanism, overexpression of PAI-1 increased the total p53 protein level [30]. The above theories further demonstrate our experimental viewpoint.…”
Section: Discussionsupporting
confidence: 69%
“…In critically ill patients with COVID-19, IL-6 signaling regulates PAI-1 production to form a positive feedback loop, leading to systemic in ammation and systemic circulation deterioration, and alleviates the severe clinical manifestations of patients by blocking IL-6 receptor [25]. Previous studies have shown that sustained PAI-1 (SERPINE1) expression leads to an increase in the percentage of cells in G2 /M phase, accompanied by a decrease in the percentage of cells in G1 phase, an increase in the level of G2 / M arrest marker P-histone H3, upregulation of pro-brotic cytokine, and ECM deposition [30]. This is in line with the results observed in this study, which showed that the number of cells in G2/M phase increased in HK-2 cells treated with myoglobin and decreased treated with tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable similarities between the development of pathologic fibrosis during injury repair and the emergence of a CAF-enriched tumor stroma, not the least of which involves the engagement of both the canonical (SMAD-dependent) and noncanonical (non-SMAD) arms of the TGF-β signaling network [ 3 , 15 , 20 , 21 , 22 , 23 , 24 , 25 ]. The growing appreciation for the congruities between fibrotic and neoplastic diseases suggests that targeting commonalities may have shared therapeutic utility [ 20 ].…”
Section: Cancer-associated Fibroblasts: Biology Of the Fibrotic Tumor...mentioning
confidence: 99%
“…14 Activation of p53 protein inhibits CDC2/cyclin B complexes essential for the G2/M transition, yielding cell cycle arrest of TECs at the G2 phase. [42][43][44] Accordingly, pharmacological inhibition or genetic deletion of p53 attenuates tubular injury and apoptosis. [45][46][47][48] We found that restoring the cell cycle with pifithrin-a treatment equalizes levels of kidney injury and renal function between the TNF PTKO and WTs during acute AAN, with similar effects on renal fibrosis in our chronic AAN model.…”
Section: Discussionmentioning
confidence: 99%